2004
DOI: 10.1113/jphysiol.2004.069468
|View full text |Cite
|
Sign up to set email alerts
|

Calf venous volume during stand‐test after a 90‐day bed‐rest study with or without exercise countermeasure

Abstract: The objectives to determine both the contribution to orthostatic intolerance (OI) of calf venous volume during a stand-test, and the effects of a combined eccentric-concentric resistance exercise countermeasure on both vein response to orthostatic test and OI, after 90-day head-down tilt bed-rest (HDT). The subjects consisted of a control group (Co-gr, n = 9) and an exercise countermeasure group (CM-gr, n = 9). Calf volume and vein cross-sectional area (CSA) were assessed by plethysmography and echography duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
2
29
1
Order By: Relevance
“…Because the popliteal vein is located isolated in the popliteal space and not directly surrounded by muscles, venous compliance was not severely influenced by the decrease in muscle mass. A similar finding was reported by Belin de Chantemele et al (2004), who found no relationship between calf muscle atrophy and calf vein deconditioning. Alternative factors that may contribute to the changes in venous compliance are alterations in the venous vessel wall Louisy et al 1997;Monahan et al 2001) or gravitational gradients within the circulation .…”
Section: Bed Rest and Venous Functionsupporting
confidence: 74%
See 3 more Smart Citations
“…Because the popliteal vein is located isolated in the popliteal space and not directly surrounded by muscles, venous compliance was not severely influenced by the decrease in muscle mass. A similar finding was reported by Belin de Chantemele et al (2004), who found no relationship between calf muscle atrophy and calf vein deconditioning. Alternative factors that may contribute to the changes in venous compliance are alterations in the venous vessel wall Louisy et al 1997;Monahan et al 2001) or gravitational gradients within the circulation .…”
Section: Bed Rest and Venous Functionsupporting
confidence: 74%
“…However, an efficient countermeasure effect of this physical exercise during deconditioning on the venous vascular system is not demonstrated yet. Resistive exercise failed to affect the response of tibial and gastrocnemial vein diameter to bed rest (Belin de Chantemele et al 2004). If vein diameter accounts for venous capacitance and compliance, and resistive vibration exercise is no effective countermeasure on a relatively spacious vein (not directly surrounded by muscle mass), it is unlikely that exercise has a protective effect on venous function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors contribute to orthostatic intolerance: moderate hypovolemia (Buckey et al 1996;Custaud et al 2002), decreased stroke volume (Buckey et al 1996), myocardial atrophy (Levine et al 1997), reduced baroreXex sensitivity (Sigaudo-Roussel et al 2002) and increased distensibility of lower extremity blood vessels (Convertino et al 1989;Belin de Chantemele et al 2004b). Furthermore, females have a lower orthostatic tolerance than males (Convertino 1998;Fu et al 2004).…”
mentioning
confidence: 99%